Gender differences in motivational crowding out of work perfomance - Volker Benndorf; Holger A. Rau; Christian Sölch (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper studies motivational crowding-out effects after financial incentives are lowered. In a real-effort setting, workers receive a piece rate before financial incentives are substituted by a one-time payment. Under the fixed payment, effort is significantly lower only when preceded by piece-rate incentives. The decrease is driven by a fraction of men who reduce their effort by 12%, whereas women constantly perform well. We find that this motivational crowding-out effect disappears when men do not have prior experience of a piece rate. In a series of control treatments, we discard all alternative explanations besides from motivational crowding out.
Keywords: C91; J16; M54; 330; gender differences; incentives; motivational crowding out; real-effort task